Narcissism as a Mediator of the Relationship between Entrepreneurial Orientation and Firm Performance - Siwar Youssef (Faculty of Business, President University, 2022)
This research aims to investigate factors influencing firm performance. Two interesting factors have been identified, namely entrepreneurial orientation and narcissism. To the best of the author’s knowledge, this is the first research to investigate narcissism in the context of firm performance in Tunisia. This quantitative research involved 89 start-ups in Tunisia, each start-up was represented by either one junior or middle manager through non-probability sampling method. This research employed Structural Equation Modelling (SEM). The data was analysed using SPSS AMOS. The results reveal that 1) entrepreneurial orientation has a positive effect on narcissism 2) entrepreneurial orientation has a positive effect on firm performance and 3) narcissism has a positive effect on performance and 4) narcissism partially mediates the relationship between entrepreneurial orientation and firm performance.